Fundamentals of Actionscript 3.0 : develop and design - Winnie, Doug (Peachpit Press, 2011)
Adobe Flash Professional is the most popular software available for creating animations for the Web. Most people start using Flash to create vector-based animations that output small file sizes perfect for the Web. Later they want to branch out into creating rich interactive experiences for websites and mobile devices, and for that they need to learn ActionScript. Doug Winnie draws on the experience he's gained from his years as an educator to teach not only what ActionScript can do, but also to show how the code works. This gives the reader a deeper understanding of how ActionScript functions, and gives them the power to come up with original solutions when creating their own projects. Doug's book dives right into the concepts of manipulating Flash objects and the fundamentals of functions and mathematical operators. After presenting events and using scripts to control the Flash timeline, classes and conditionals are covered in depth. The final part of the book covers creating desktop applications with Adobe AIR, developing mobile applications, and working with external code libraries. Real-world projects are sprinkled generously throughout the book and Appendices include information on debugging, deciphering documentation, and using Adobe Flash Builder as an ActionScript development environment.